Multi-criteria site selection for solid waste disposal: integration of center of gravity and AHP-GIS analysis in Guayas, Ecuador - Aguiñaga-Vallejo, Marcela; Paredes-Verduga, Cecilia; Jácome-Cornejo, María; Briones-Bitar, Josué; Jaya-Montalvo, María; Morante-Carballo, Fernando; Suárez-Zamora, Sebastián; Aguilar-Aguilar, Maribel; Berrezueta, Edgar; Carrión-Mero, Paúl (Frontiers in Sustainability, 2025)
IntroductionThe selection of optimal sites for solid waste disposal is a critical aspect of management, especially from an environmental and logistical perspective. In Guayas province (Ecuador), many solid waste disposal sites have been implemented without technical-environmental planning, exacerbated by financial constraints that hinder their effective management. Given this context, this study proposes integrating the concept of the Gravity Center of Waste Production (GCWP) into the traditional criteria for selecting Final Disposal Sites (FDS) by combining Analytical Hierarchical Analysis (AHP) and geographic information systems, strengthening logistics management and the development of inter-municipal partnerships in the north of Guayas province.MethodsThe study addressed a diagnostic stage, the evaluation of FDS selection criteria, and the identification of suitable areas through mapping.ResultsThe municipalities present limitations for the adequate operation of FDS, most of which are open-air dumps. Therefore, three groups were proposed as possible partnerships between cantons. The AHP analysis showed that criteria related to water conservation were the highest-scoring, as opposed to land use and land cover. The selected sites are as close as possible to the GCWP for optimal waste disposal. The results were validated through the analysis of four different scenarios and the participation of authorities in charge of territorial management.DiscussThe proposed methodological approach is a viable alternative for cantons, districts, or municipalities with budgetary constraints, as it seeks to be a helpful management tool for waste disposal within a framework of intermunicipal cooperation.